2013
DOI: 10.1097/inf.0b013e3182a72fc0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rotavirus Vaccine on Childhood Diarrheal Hospitalization After Introduction Into the South African Public Immunization Program

Abstract: Using published estimates of rotavirus hospitalization burden, we estimate that at least 13,000 to 20,000 hospitalizations in children <2 years were prevented in the 2 years after rotavirus vaccine introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 27 publications
3
52
0
1
Order By: Relevance
“…First, declines were concentrated during the rotavirus season months, with the great majority of annual reductions occurring in May through October, as has been described in other settings after introduction of rotavirus vaccination [13][14][15]22]. Second, declines in deaths and hospitalizations were most pronounced among infants, which correlated with the higher burden of severe rotavirus in this age group [20], as well as with the higher vaccine coverage among infants during the study period.…”
Section: Discussionmentioning
confidence: 60%
“…First, declines were concentrated during the rotavirus season months, with the great majority of annual reductions occurring in May through October, as has been described in other settings after introduction of rotavirus vaccination [13][14][15]22]. Second, declines in deaths and hospitalizations were most pronounced among infants, which correlated with the higher burden of severe rotavirus in this age group [20], as well as with the higher vaccine coverage among infants during the study period.…”
Section: Discussionmentioning
confidence: 60%
“…[25] Subsequent studies of the public health impact of these vaccines have shown a beneficial effect. [25][26][27] These data demonstrate a similar trend in the incidence and mortality of severe diarrhoea and pneumonia in under-5 children, which coincides with the introduction of new vaccines and may be due to an actual decline in population incidence and reduced severity of disease. However, other contributing factors, such as improvements in access to and treatment at lower levels of care, and improvements in access to …”
Section: Researchmentioning
confidence: 56%
“…Some countries have included this vaccine in the national vaccination program and achieved very good vaccination coverage in infants. In those countries, rotavirus incidence and hospitalization rates for rotavirus gastroenteritis have decreased significantly (Buttery et al, 2011;Dennehy, 2012;Msimang et al, 2013;Payne et al, 2013;Standaert et al, 2013;Vesikari et al, 2013). The effectiveness of the two rotavirus vaccines was confirmed in large prelicensure clinical trials and they showed good protection for the most common rotavirus genotypes (Ruiz-Palacios et al, 2006;Vesikari et al, 2006).…”
Section: Introductionmentioning
confidence: 87%